The Impact of Seasonal Climate Conditions on Fungal Biodiversity in Barn Air - Giray, G; Şimşek, A (Journal of the Hellenic Veterinary Medical Society, 2026)
This study examines the seasonal effects of climatic variables on fungal biodiversity in the indoor air of cattle barns in Turkey. Over 12 months, air samples were collected twice a month from 10 cattle barns, resulting in isolating 72 fungal species from 18 genera by using sophisticated microbiological sampling and MALDI-TOF MS identification techniques. Dominant genera such as Acremonium, Alternaria, Aspergillus, Cladosporium, and Penicillium were detected throughout the year, underlining their continuous presence. Seasonal variability is evident, with Cladosporium and Alternaria in high amount in warmer months, while Penicillium is more prevalent in colder months. Environmental variables, including temperature and humidity, strongly correlated with fungal concentrations, and ideal ranges were identified for the major species. These findings highlight the health hazards of airborne fungal spores to cattle and barn workers and focus on the need for improved air quality management techniques in livestock facilities. The study constitutes a fundamental understanding of fungal distribution and environmental interactions and calls for further in-depth research to mitigate health hazards and improve barn air quality.